PENGARUH PENGUNGKAPAN AKUNTANSI LINGKUNGAN DAN CSR TERHADAP KINERJA KEUANGAN PERUSAHAAN SUBSEKTOR FARMASI DI BURSA EFEK INDONESIA TAHUN 2018-2021 - Enjelina Situmeang; Thezar Fiqih Hidayat Hasibuan; Rana Fathinah Anada; Fauziah Rahman (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This research aims to determine the effect of environmental accounting and corporate social responsibility disclosures on the financial performance of pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. Environmental accounting disclosures will encourage the ability to minimize environmental problems faced by the Company, problems of environmental damage, their causes and their impact on human life both now and in the future. This encourages people to realize the importance of environmental conservation. This research uses quantitative methods. The sample in this research was 36 data collection using the company's annual report. Sampling used total sampling and the significance level used was 0.05. Based on research results, Environmental Accounting positively and significantly influences financial performance, Corporate Social Responsibility positively and significantly influences financial performance, Environmental Accounting disclosure and Corporate Social Responsibility simultaneously influence the financial performance of Pharmaceutical Sub-Sector Manufacturing Companies Listed on the Stock Exchange Indonesia in 2018-2021.